UJI EFEK ANTIMIKROBA EKSTRAK DAUN PUTRI MALU (MIMOSA PUDICA DUCHAAS & WALP) SECARA IN VITRO - Mehingko, Lieken; Awaloei, Henoch; Wowor, Mona P. (Jurnal Biomedik : JBM, 2010)
Abstract: The â€œsensitive plantâ€ (Mimosa pudica Duchaas & Walp) is categorized as a spreading weed. Its existence is threatened due to the assumption that it has no positive qualities. However, parts of this plant, including roots, stems, and leaves, either fresh or dried, have been used as a traditional medicine. Based on the benefits of this plant in conjunction with increases of infectious diseases due to microbes, research into the antimicrobial effects of the extract of this plant in vitro has to be developed much more. The result of this study was that antimicrobial effects of this â€œsensitiveâ€ plantâ€™s leaf extract, at a concentration of 100%, was more effective than at concentrations of 50% or 33%, based on the diameters of the zones of inhibition where no microbes grew. Keywords: antimicrobial, in vitro, Mimosa pudica Duchaas & Walp. Â  Â  Abstrak: Tumbuhan Putri malu (Mimosa pudica Duchaas & Walp) tergolong rumput liar yang terancam keberadaannya karena sering dianggap gulma yang merugikan tanaman budidaya. Seluruh bagian tanaman ini dapat berkhasiat sebagai obat mulai dari akar, batang, dan daun, baik dalam bentuk segar ataupun yang dikeringkan. Berdasarkan manfaat dari tumbuhan putri malu serta semakin meningkatnya penyakit infeksi yang disebabkan oleh bakteri maka perlu dilakukan penelitian uji efek antimikroba dari ekstrak daun putri malu secara in vitro. Hasil penelitian memperlihatkan efek antimikroba ekstrak daun putri malu dengtan konsentrasi 100% lebih efektif daripada konsentrasi 50% dan 33% dengan berpatokan pada panjangnya diameter zona hambat yang terbentuk oleh masing-masing bakteri uji. Kata kunci: antimikroba, in vitro, putri malu.